LINC00152 Promotes Tumor Progression and Predicts Poor Prognosis by Stabilizing BCL6 From Degradation in the Epithelial Ovarian Cancer - Wang, Shunni; Weng, Weiwei; Chen, Tingting; Xu, Midie; Wei, Ping; Li, Jing; Lu, Linghui; Wang, Yiqin (Frontiers in Oncology, 2020)
Long non-coding RNA 00152 (LINC00152) is tumorigenic in multiple somatic malignancies. However, its prognostic significance and molecular mechanisms in the epithelial ovarian cancer (EOC) remain elusive. Here our study reveals that dysregulation of LINC00152 is a predictor of poor prognosis in patients with EOC and facilitates ovarian tumor growth and metastasis both in vitro and in vivo; the expression of LINC00152 positively correlates with the protein levels of BCL6 in EOC tissues and ovarian tumor cells; LINC00152 binds to Ser333 and Ser343 of BCL6 protein and stabilizes BCL6 from poly-ubiquitination thus facilitating the oncogenic functions in EOC. Moreover, overexpression of the mutant BCL6S333A/S343A fails to rescue the reduced proliferation and invasion caused by the knockdown of endogenous BCL6 in LINC00152-overexpressing cells. Our study might not only offer clues to the network of lncRNA-protein interactions but also provide potential therapeutic targets for the tumor pharmacology. Statement of Significance: This work reveals that dysregulation of LINC00152 in ovarian cancer predicts poor survivals of patients, and the stabilization of BCL6 by LINC00152 promotes ovarian tumor proliferation and invasion.